Artificial Intelligence and New Frontiers in Scientific Communication: Inteligencia artificial y nuevas fronteras en la comunicación científica - Morales, Juan (2025)
Human cognitive activity is irreplaceable in the generation of knowledge. The ethical integrity of all those involved in scientific research and publication constitutes the strongest safeguard against the inappropriate use of artificial intelligence. The future of scientific communication will depend, to a great extent, on our ability to integrate these technologies with responsibility, prudence, and a commitment to truth.